Perovskite‐Based Optoelectronic Biointerfaces for Non‐Bias‐Assisted Photostimulation of Cells. Issue 17 (11th July 2019) - Aria, Mohammad M.; Srivastava, Shashi B.; Sekerdag, Emine; Dikbas, Ugur M.; Sadeghi, Sadra; Pering, Samuel R.; Cameron, Petra J.; Gursoy‐Ozdemir, Yasemin; Kavakli, Ibrahim H.; Nizamoglu, Sedat
Abstract: Organohalide perovskites have attracted significant attention for efficient solar energy harvesting. They boost the photoelectrical conversion efficiency of the solution‐processable solar cells because of having a nearly 100% internal quantum efficiency, operating in both narrow‐ and broadband spectral regimes, near‐infrared sub‐bandgap absorption, and high diffusion length. At the same time, these optoelectronic properties make it an ideal candidate for photostimulation of neurons. However, the biocompatibility of perovskite and its longevity in a cell medium constitute a major limitation to use it for biological interfaces. Here, high‐level perovskite stability and biocompatibility are shown by forming hydrophobic perovskite microcrystals and encapsulating them within a polydimethylsiloxane layer. For effective and safe photostimulation of cells perovskite microcrystals are interfaced with poly(3‐hexylthiophene‐2, 5‐diyl) (P3HT) polymer for dissociation of the photogenerated charge carriers, which leads to non‐bias‐assisted cell stimulation. The results point out a new direction for the use of perovskite for photomedicine. Abstract : Biocompatible neural interfaces utilizing organohalide perovskites are achieved via polymeric encapsulation of hydrophobic perovskite microcrystals in optoelectronic device structure operating under physiological conditions. The interface stimulates cells by converting light to bioelectrical currents without any external battery or circuitry.